FACTORS INFLUENCING THE COMPRESSIVE STRENGTH OF FLY ASH-BASED GEOPOLYMER CONCRETE - Djwantoro Hardjito; Steenie E Wallah; Dody M.J. Sumajouw; B.V Rangan (Civil Engineering Dimension, 2004)
This paper describes the effects of several factors on the properties of fly ash based geopolymer concrete, especially the compressive strength. The test variables included were the age of concrete, curing time, curing temperature, quantity of superplasticizer, the rest period prior to curing, and the water content of the mix. The test results show that the compressive strength of geopolymer concrete does not vary with age, and curing the concrete specimens at higher temperature and longer curing period will result in higher compressive strength. Furthermore, the commercially available Naphthalene-based superplasticizer improves the workability of fresh geopolymer concrete. The start of curing of geopolymer concrete at elevated temperatures can be delayed at least up to 60 minutes without significant effect on the compressive strength. The test data also show that the water content in the concrete mix plays an important role.